Association between total functional tooth unit score and hemoglobin A1c levels in Japanese community-dwelling individuals: the Nagasaki Islands study - Masayuki Oohira; Masayasu Kitamura; Kanako Higuchi; Mark Luigi Fabian Capati; Mami Tamai; Saki Ichinose; Yumiko Kawashita; Sakiko Soutome; Takahiro Maeda; Atsushi Kawakami; Atsutoshi Yoshimura (BMC, 2024)
Abstract Background It is widely recognized that periodontal disease is associated with diabetes mellitus. Periodontal disease is accompanied by inflammation of the periodontal tissue, impaired masticatory function, and the presence of periodontopathic bacteria, all of which may affect glycemic control. However, the exact relationship between these factors and glycemic control has not yet been established. In this study, we aimed to investigate the relationship between periodontal disease-related factors and glycemic control in Japanese community-dwelling individuals. Methods We conducted a cross-sectional study involving 671 participants aged 29-92 (65.3 ± 12.1) years, using data from the Nagasaki Islands Study. Participants underwent routine medical examinations, including body mass index (BMI) and hemoglobin A1c (HbA1c) levels. Information on the participants' demographics (age and sex) and whether they were on diabetes medications, had an exercise habit, consumed alcohol, engaged in late-night eating, had regular dental checkups, and smoked was obtained using a self-administered questionnaire. Dental examinations were performed to examine dentition status, probing pocket depth, clinical attachment level (CAL), and bleeding on probing. Functional tooth units (FTUs), defined as pairs of occluding posterior teeth, were used as an indicator of occlusal support area. Saliva samples were collected and levels of two species of periodontopathic bacteria (Porphyromonas gingivalis and Aggregatibacter actinomycetemcomitans) were determined using real-time polymerase chain reaction. We analyzed the association between HbA1c levels and variables related to periodontal status, masticatory function, and salivary levels of periodontopathic bacteria. Results Bivariate analysis showed that HbA1c levels were significantly associated with age, sex, exercise habit, BMI, diabetes medications, CAL, salivary P. gingivalis level, number of teeth, and three FTU subcategories. In the multiple regression analysis, age, BMI, diabetes medications, and total FTU score (i.e., including natural teeth, implant-supported artificial teeth, fixed prostheses, and removable dentures) remained associated with HbA1c levels (B = 0.23, 0.14, 0.52, and − 0.12; p < 0.001, p < 0.001, p < 0.001, and p = 0.008, respectively). Conclusions In this community-based cross-sectional study, total FTU was significantly associated with HbA1c levels, independent of other risk factors. This suggests that reconstructed occlusal support areas, including dentures, are associated with glycemic control in the older population.